PENGARUH KEPERCAYAAN MEREK DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI MEDIASI PERSEPSI NILAI PELANGGAN - Dhirtya, Desak Ayu Made Citta; Warmika, I Gede Ketut (E-Jurnal Manajemen; Vol 11 No 3 (2022)DO - 10.24843/EJMUNUD.2022.v11.i03.p07, 2022)
The purpose of this study was to analyze the effect of brand trust, service quality and customer value perception on customer loyalty on the Bukalapak site, to analyze the influence of brand trust and service quality on customer value perception on the Bukalapak site, and to analyze the effect of customer value perception mediating brand trust and quality of service to customer loyalty on the Bukalapak site. The population in this study are social media users who make online transactions on the Bukalapak site with certain considerations. The sample is determined by the non probability sampling technique, which is 150 respondents. The data collection method uses a questionnaire. The data analysis technique used in this study is Path Analysis. The results showed that brand trust, service quality and customer value perceptions had a positive and significant effect on customer loyalty. The results showed brand trust and service quality had a positive and significant effect on customer value perception. The results also indicate the perception of customer value is able to mediate the influence of brand trust and service quality on customer loyalty. Keywords: brand trust, service quality, customer value, customer loyalty